The Interface Thermal Resistance Evolution between Carbide-Bonded Graphene Coating and Polymer in Rapid Molding for Microlens Array - Liu, Xiaohua (Polymers (Basel), 2021)
Surface rapid heating process is an efficient and green method for large-volume production of polymer optics by adopting 3D graphene network coated silicon molds with high thermal conductivity. Nevertheless, the heat transfer mechanism including the interface thermal resistance evolution between 3D graphene network coating and polymer has not been thoroughly revealed. In this study, the interface thermal resistance model was established by simplifying the contact situation between the coating and polymethylmethacrylate (PMMA), and then embedding into the finite element method (FEM) model to study the temperature variations of PMMA in surface rapid heating process. Heating experiments for graphene network were then carried out under different currents to provide the initial heat for heat transfer model. In addition, residual stress of the PMMA lens undergoing the non-uniform thermal history during molding was presented by the simulation model together. Finally, the optimal molding parameters including heating time and pressure will be determined according to calculation results of the interface thermal resistance model and microlens array molding experiment was conducted to illustrate that the interface thermal resistance model can predict the temperature of the polymer to achieve a better filling of microlens array with smooth surface and satisfactory optical performance.